Strategi Industrialisasi “Pola IKM Dan UMKM Di Surabaya” - Faisal Restu Ardiansyah; Siti Nur Amalia; Muhammad Yasin (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This paper discusses the industrialization strategy with a focus on the pattern of Small and Medium Industries (IKM) and Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Industrialization has become one of the important efforts to drive a country's economic growth. In the Indonesian context, SMEs and SMEs have a significant role in economic development and job creation. This paper outlines existing patterns in the SMI and MSMEs industry in Indonesia, and describes strategies that can be used to encourage the industrialization of these sectors. In this analysis, several important factors will be discussed, including government policy support, infrastructure development, access to capital and technology, and capacity building and training.